Lip response to incisor movement in operated cleft lip and palate patients - Vignesh Kailasam; Nithya Jagdish; Sunitha Chakravarthy; Arun B Chitharanjan (Wolters Kluwer Medknow Publications, 2017)
Background: Although the literature has shown that the lip response to maxillary incisor retraction varies, these studies have been done on a noncleft lip/palate sample. Aim: The aim of this study is to evaluate response of operated cleft lip to orthodontic tooth movement and to determine if there are any differences in the response between the operated cleft lip and the noncleft lip. Settings and Design: This was a hospital-based retrospective study using radiographs. Materials and Methods: Lip changes were evaluated using pre- and post-operative lateral cephalometric radiographs. The experimental group consisted of 12 patients with operated cleft lip while the control group consisted of 12 noncleft patients with dental and skeletal Class I malocclusion. Statistical Analysis: ANOVA was used for statistical analysis. Results: The operated lip responded less to incisor movement than the noncleft group (P < 0.05). While the cleft group demonstrated an increase in upper lip thickness measurements at Point A and vermilion following incisor retraction, the control group showed a decrease in thickness of the upper lip at Point A and an increase at vermilion. Conclusion: The cleft team should be aware that the operated lip responds differently to incisor movement. This will enable them to better plan comprehensive treatment for the cleft lip and palate patient.